An entrepreneurial view of universal work-integrated learning. Issue 4 (20th April 2020) - Dorland, AnneMarie; Finch, David J.; Levallet, Nadège; Raby, Simon; Ross, Stephanie; Swiston, Alexandra
Abstract : Purpose: Work-integrated learning (WIL) has emerged as a leading pedagogy that blends theory with application. In recent years, policymakers, educators and practitioners have called for a significant expansion of WIL, one which would enable every undergraduate student has at least one WIL experience during their program of study. Despite these appeals, there remains a significant divide between the aspiration of universality and the realities. Consequently, the study asks the following question: How can post-secondary institutions expand their WIL initiatives to universal levels that deliver transformative learning? Design/methodology/approach: In this exploratory study, the authors leverage research from entrepreneurship and management to develop a conceptual model of universal work-integrated learning (UWIL). Entrepreneurship and management research is relevant in this context, as the rapid introduction of a UWIL has transformative implications at the level of the individual (e.g. students, faculty), organization (e.g. processes) and the learning ecosystem (e.g. partners, policymakers) — issues at the core of research in entrepreneurship and management over the past two decades. Findings: At the core of the authors' proposal is the contention that the high-impact talent challenge and the delivery of UWIL must be reframed as not simply a challenge facing educators, but as a challenge facing the broader ecosystem of the workforce and the larger community. The authors propose the implementation of UWIL through an open innovation framework based on five strategic pillars. Originality/value: Ultimately, the findings the authors present here can be leveraged by all members of the learning ecosystem, including administrators, faculty, policymakers, accreditation bodies and community partners, as a framework for operationalizing a UWIL strategy. The study's model challenges all members of this learning ecosystem to operationalize a UWIL strategy. This entrepreneurial reframing introduces the potential for innovating the delivery of UWIL by leveraging the broader learning ecosystem to drive efficiencies and transformative learning.